A large-scale RNAi screen in human cells identifies new components of the p53 pathway - Berns, Katrien; Hijmans, E. Marielle; Mullenders, Jasper; Brummelkamp, Thijn R.; Velds, Arno; Heimerikx, Mike; Kerkhoven, Ron M.; Madiredjo, Mandy; Nijkamp, Wouter; Weigelt, Britta; Agami, Reuven; Ge, Wei; et al. (Nature, 2004)
RNA interference (RNAi) is a powerful new tool with which to perform loss-of-function genetic screens in lower organisms and can greatly facilitate the identification of components of cellular signalling pathways 1 , 2 , 3 . In mammalian cells, such screens have been hampered by a lack of suitable tools that can be used on a large scale. We and others have recently developed expression vectors to direct the synthesis of short hairpin RNAs (shRNAs) that act as short interfering RNA (siRNA)-like molecules to stably suppress gene expression 4 , 5 . Here we report the construction of a set of retroviral vectors encoding 23,742 distinct shRNAs, which target 7,914 different human genes for suppression. We use this RNAi library in human cells to identify one known and five new modulators of p53 -dependent proliferation arrest. Suppression of these genes confers resistance to both p53 -dependent and p19 ARF -dependent proliferation arrest, and abolishes a DNA-damage-induced G1 cell-cycle arrest. Furthermore, we describe siRNA bar-code screens to rapidly identify individual siRNA vectors associated with a specific phenotype. These new tools will greatly facilitate large-scale loss-of-function genetic screens in mammalian cells.